Developing flip chart as career counseling media for college major selection for the students - Firdayanti Rukmana; Syamsul Bachri Thalib; Abdullah Pandang; Ahmad Yasser Mansyur (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
The primary issue of this research is the development of career guidance and counseling medium. This research aims at identifying (1) an illustration of necessity level of the development toward the career guidance and counseling flipchart medium in choosing major in university towards students of SMAN 1 Tanggetada. (2) The prototype of career guidance and counseling medium of choosing major in University towards student of SMAN 1 Tanggetada. (3) The validity and the practical media of career Guidance and Counseling medium of flipchart in choosing major in University towards students of SMAN 1 Tanggetada. This research applies researching model of ADDIE which consists of 5 (five) steps of research. The technique of collecting data uses interview and questionnaire. The results shows ; (1) the result of necessity analysis conducted in SMAN 1 Tanggetada shows that the teachers of Guidance and Counseling and the students need career guidance and counseling flipchart medium in choosing major in university; (2) the prototyped career guidance and counseling flipchart medium in choosing major in university consist of Flipchart, Guideline book and material as well as reading script concerning to career; (3) the result of validity and practicable show that career guidance and counseling flipchart medium is valid and practice therefore deserved to be applied in SMAN 1 Tanggetada to help students in choosing major at university.